Optimism without theism? Nagasawa on atheism, evolution, and evil - Kahane, G (Cambridge University Press, 2021)
Nagasawa has argued that the suffering associated with evolution presents a greater challenge to atheism than to theism because that evil is incompatible with ‘existential optimism’ about the world—with seeing the world as an overall good place, and being thankful that we exist. I argue that even if atheism was incompatible with existential optimism in this way, this presents no threat to atheism. Moreover, it’s unclear how the suffering associated with evolution could on its own undermine existential optimism. Links between Nagasawa argument and the current debate about the axiology of (a)theism are also explored.